Analysis of Consumer Behavior and Purchase Decisions in the Phenomenon of Pertamax Fuel Adulteration: A Case Study on the Shift to Shell Fuel in Urban Areas of Indonesia - Fadillah Fadillah; Usep Suhud; Setyo Ferry Wibowo (Greenation International Journal of Economics and Accounting, 2025)
This study investigates the shift in consumer behavior and purchase decisions from Pertamax to Shell fuel in urban areas of Indonesia, with a focus on understanding the factors influencing this change. The objective was to explore the underlying motivations driving consumers to choose Shell over Pertamax, examining the role of price sensitivity, perceived fuel quality, brand trust, and promotional factors. A qualitative approach was employed, utilizing open-ended questionnaires to gather in-depth insights from 103 participants across major urban areas in Indonesia. The data analysis was conducted using an interactive model, which included data reduction, display, and conclusion drawing. Results revealed that the primary motivations for choosing Shell included its perceived superior fuel quality, better vehicle performance, and smoother driving experience. Additionally, service quality at Shell stations contributed to customer satisfaction. Despite the positive feedback, a significant number of consumers expressed price sensitivity, with many indicating they would consider switching back to Pertamax if it improved its pricing or quality. The findings underscore the importance of both economic and psychological factors in consumer decision-making in the Indonesian fuel market.